Proteostasis failure and cellular senescence in long‐term cultured postmitotic rat neurons - Ishikawa, Shoma; Ishikawa, Fuyuki (Aging cell, 2020)
Cellular senescence, a stress‐induced irreversible cell cycle arrest, has been defined for mitotic cells and is implicated in aging of replicative tissues. Age‐related functional decline in the brain is often attributed to a failure of protein homeostasis (proteostasis), largely in postmitotic neurons, which accordingly is a process distinct by definition from senescence. It is nevertheless possible that proteostasis failure and cellular senescence have overlapping molecular mechanisms. Here, we identify postmitotic cellular senescence as an adaptive stress response to proteostasis failure. Primary rat hippocampal neurons in long‐term cultures show molecular changes indicative of both senescence (senescence‐associated β‐galactosidase, p16, and loss of lamin B1) and proteostasis failure relevant to Alzheimer's disease. In addition, we demonstrate that the senescent neurons exhibit resistance to stress. Importantly, treatment of the cultures with an mTOR antagonist, protein synthesis inhibitor, or chemical compound that reduces the amount of protein aggregates relieved the proteotoxic stresses as well as the appearance of senescence markers. Our data propose mechanistic insights into the pathophysiological brain aging by establishing senescence as a primary cell‐autonomous neuroprotective response. Loss of protein homeostasis (proteostasis) is a hallmark of brain aging, yet the adaptive mechanism that contributes to life‐long neuronal preservation is poorly understood. Long‐term cultures of primary post‐mitotic neurons increase a proteotoxic burden and establish cellular senescence, which is alleviated by prolonged treatment of neurons with rapamycin. Post‐mitotic cell senescence is accompanied by stress resilience, suggesting an intrinsic neuroprotective role of senescence.